Biochemical characterization of Indian mustard (Brassica juncea L.) genotypes in response to moisture stress and irrigation modules (Journal of Oilseed Brassica, 2026)
In the current investigation, the impact of moisture stress and irrigation modules was studied on biochemical characteristics in twelve Brassica juncea genotypes. Experiment was laid in split plot design with three moisture treatments viz. only pre sowing irrigation (I0), one irrigation at 35 DAS (I1) and two irrigations, one at 35 DAS and second at 65 DAS (I2).Water stress up-regulated the sugars and proline content in the genotypes while it reduced the protein content. Highest amount of total sugars was recorded in K-9-108 (70.3 mg g-1 DW), reducing sugars in RLC1 (12.61 mg g-1 DW), protein content in MLM-19 and NLM-3 (8.8 mg g-1DW) while highest proline was in NPJ-79 (0.87mg g-1 DW) under moisture stress. Genotypes differed significantly for the biochemical constituents and total soluble proteins increased progressively with one and two irrigations.